2001
DOI: 10.1598/rrq.36.4.5
|View full text |Cite
|
Sign up to set email alerts
|

The Journey Ahead: Thirteen Teachers Report How the Internet Influences Literacy and Literacy Instruction in Their K‐12 Classrooms

Abstract: S The purpose of this study was to explore 13 K‐12 teachers' reports of how the Internet influenced literacy and literacy instruction in their classrooms. The teachers, including ten women and three men, represented 11 different states in the U.S. and were considered exemplary at using technology by their colleagues. Labbo and Reinking's (1999) notion of multiple realities in relation to new technologies provided a framework for understanding the participants' perspectives of the Internet's relationship to lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 24 publications
1
63
0
2
Order By: Relevance
“…This perception was supported by both the observations of and interviews with students of different ages, as well as the study of Buckingham and colleagues (2011). Referring to an inspiring effect on the learners, though weakening with age, this finding about online publishing for an authentic public is consistent with the results of Karchmer (2008). Accordingly, an observation of sChOOLtv revealed that few videos produced by secondary students had been published there.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…This perception was supported by both the observations of and interviews with students of different ages, as well as the study of Buckingham and colleagues (2011). Referring to an inspiring effect on the learners, though weakening with age, this finding about online publishing for an authentic public is consistent with the results of Karchmer (2008). Accordingly, an observation of sChOOLtv revealed that few videos produced by secondary students had been published there.…”
supporting
confidence: 87%
“…Publishing-oriented media production motivates learners to create content (Lange & Ito, 2010) and 4 improve the quality of products (Butler et al, 2010;Karchmer, 2008). Furthermore, online publishing may promote reflective online interactions (Kearney, 2009).…”
Section: Culture Of Media Encouragementmentioning
confidence: 99%
“…Ils y sont rapidement confrontés à leur propre limites au regard des connaissances scientifiques qui doivent être détenues afin de faire un choix éclairé dans la sélection et l'analyse de l'information accessible sur Internet (Clark et Slotta, 2000). En conséquence, la majorité des praticiennes et des praticiens tendent à considérer le recours pédagogique aux TIC comme ayant une utilité restreinte, soit sur le plan de la préparation de l'enseignement, en général dans le cadre de matières scolaires particulières, soit encore sur celui de l'enrichissement du matériel didactique mis à la disposition des élèves (Karchmer, 2001). Lorsque c'est le cas, ils intègrent ces ressources de façon limitée, habituellement en invitant les élèves à utiliser des cédéroms pour des recherches ou en les incitant à visiter certains sites Internet présélectionnés, presque toujours pour l'enseignement de matières scolaires spécifiques (Van Braak, 2001 ;Yaghi, 2001).…”
Section: Alphabétisation Informatique Compétence Informatique Et Prounclassified
“…Karchmer [21] explored 13 K-12 teachers' reports of how the Internet influences literacy and literacy instruction in their classroom. He used constant-comparative data analysis that included e-mail interviews, participants' reflective journals, web pages, online articles, and lesson plans to discover how the teachers viewed the Internet's influence on reading as an extension of traditional literacy skills.…”
Section: A Technology and Literacymentioning
confidence: 99%